2023
DOI: 10.2196/43730
|View full text |Cite
|
Sign up to set email alerts
|

The Usability, Feasibility, Acceptability, and Efficacy of Digital Mental Health Services in the COVID-19 Pandemic: Scoping Review, Systematic Review, and Meta-analysis

Abstract: Background After the rapid spread of the novel SARS-CoV-2, the short-term and long-term mental health impacts of the pandemic on the public, in particular on susceptible individuals, have been reported worldwide. Although digital mental health services expand accessibility while removing many barriers to in-person therapy, their usability, feasibility, acceptability, and efficacy require continued monitoring during the initial phase of the pandemic and its aftermath. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 83 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…Since adapting to COVID-19 and utilising remote assessments, emerging research regarding digital mental health services has shown preliminary support for the efficacy and feasibility of online services ( 36 , 37 ), for a recent meta-analysis). Therefore, we posed the question: can virtual attachment assessments be employed going forward, given the use of telehealth that has remained even past the pandemic, and are there things to be learned from this case study?…”
Section: Discussionmentioning
confidence: 99%
“…Since adapting to COVID-19 and utilising remote assessments, emerging research regarding digital mental health services has shown preliminary support for the efficacy and feasibility of online services ( 36 , 37 ), for a recent meta-analysis). Therefore, we posed the question: can virtual attachment assessments be employed going forward, given the use of telehealth that has remained even past the pandemic, and are there things to be learned from this case study?…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has accelerated the use of web-based applications across multiple areas of health care, including mental health services [ 38 ]. The trend toward using DMHIs as part of routine care for those seeking treatment for mental health concerns is expected to continue.…”
Section: Discussionmentioning
confidence: 99%
“…The utilisation of smartphone-based technologies has several benefits including improved usability, integration into existing use patterns, built-in app alerts, and easier facilitation of remote data management and adherence monitoring 10,[19][20][21][22] . While smartphone apps have been increasingly used in research 10,[19][20][21][22] , their application for symptomatic respiratory illness detection in cohort studies requires further exploration. Here, we present the development, implementation, and validation of an in-house smartphone app named AERIAL TempTracker and its real-world application in two cohort studies 5 .…”
Section: Introductionmentioning
confidence: 99%